2020
DOI: 10.1186/s12885-020-6606-0
|View full text |Cite
|
Sign up to set email alerts
|

Young-onset colorectal cancer in the North East of Scotland: survival, clinico-pathological features and genetics

Abstract: Background: Colorectal cancer (CRC) in patients aged under 55 years is on the rise, constituting approximately 10% of cases. Our aim was to determine the survival and clinico-pathological details of young-onset CRC (yCRC), as well as audit the referral rate to genetic services and thus establish the incidence of inherited cancer syndromes. Methods: A retrospective case note review was conducted for patients aged under 55 years who were diagnosed with CRC between 2005 and 2015 in the North East of Scotland. Cas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
4
1
Order By: Relevance
“…The sample size of these studies ranged between 49 and 64,068 cases [ 5 , 7 – 18 , 48 , 56 58 ] and the mean age of study subjects ranged between 37 and 47 years [ 5 , 7 – 12 , 14 18 ]. In contrast to our study, the frequency of early-onset CRC is generally reported to be higher in men than in women [ 5 , 7 , 10 , 11 , 13 17 , 48 ], but various studies have yielded conflicting results [ 10 , 28 , 47 , 59 ]. Without finding any reason for the gender difference, we noted that early-onset CRC predominantly affected women, whereas late-onset CRC mainly involved men, which was statistically significant.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The sample size of these studies ranged between 49 and 64,068 cases [ 5 , 7 – 18 , 48 , 56 58 ] and the mean age of study subjects ranged between 37 and 47 years [ 5 , 7 – 12 , 14 18 ]. In contrast to our study, the frequency of early-onset CRC is generally reported to be higher in men than in women [ 5 , 7 , 10 , 11 , 13 17 , 48 ], but various studies have yielded conflicting results [ 10 , 28 , 47 , 59 ]. Without finding any reason for the gender difference, we noted that early-onset CRC predominantly affected women, whereas late-onset CRC mainly involved men, which was statistically significant.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, we found that more than 39% of our cases were first diagnosed with CRC when still under 50 years. We also found that the mean age for early-onset CRCs was 40 years and that the highest number of cases were in the final decade of the age range investigated (40–50 years of age), which is in accordance with other studies [ 9 , 11 , 16 , 48 ]. However, this pattern is more pronounced in Asia than in the Western countries [ 38 , 49 55 ].…”
Section: Discussionsupporting
confidence: 92%
“…Colorectal cancer is the third most death causing cancer worldwide [ 104 , 105 ]. In colorectal cancer patients, 5-year survival rate generally after diagnosis is around 50–55% [ 106 ]. Chemotherapy for colorectal cancer is the ideal choice of intervention but drug resistance often hampers the success of therapy.…”
Section: Various Molecular Targets Affected By Sabmentioning
confidence: 99%
“…The reduced cancer-mortality is attributable to population-based screenings and significant progresses in therapeutic options improving CRC patient’s management [ 2 ]. Approximately 10% of CRC patients under 55 years showed more severe and unfavorable pathological features than older cohorts, resulting in a negative impact on their survival outcome [ 3 ].…”
Section: Introductionmentioning
confidence: 99%